Three new species of Microbrotula (Teleostei: Ophidiiformes: Bythitidae) from the Indo-West Pacific - Anderson, M. Eric (Zootaxa, 2005)
Three new species of the rare Indo-Pacific fish genus Microbrotula are described. Microbrotula bentleyi sp. n. is known in the western Indian Ocean from the Gulf of Aqaba, Red Sea, and South Africa. Two species occur off Queensland, Australia, M. polyactis sp. n. and M. queenslandica sp. n. The species of Microbrotula are distinguished mainly on the basis of counts of the axial skeleton, scale rows and pectoral-fin rays, but some morphometric characters are also diagnostic, such as orbit diameter, predorsal length and fleshy interorbital width. All species live in coral-reef or rubble areas to depths of about 50 m. New material of M. randalli Cohen and Wourms, 1976 was studied and Microbrotula is re-diagnosed.